Christianity, good health and vegetarianism in Japan, c. 1900-45 - Fujimoto, Hiroshi (Food & history, 2022)
Western food cultures have been popular in Japan since the middle of the nineteenth century. Although meat-based diets spread quickly among the Japanese population at the turn of the twentieth century, some Japanese groups, particularly socialists and Seventh Day Adventists, were attracted to Western vegetarianism. Both socialists and Adventists enthusiastically discussed the significance of vegetarianism, but socialists soon lost interest. In contrast, Japanese Adventists have continued to follow meatless diets, and the Japanese Seventh Day Adventist Church remains one of the leading promoters of vegetarianism in Japan. However, food historians have paid little attention to their role in spreading vegetarianism in Japan. This article examines how Japanese Adventists adopted and developed meatless diets, comparing their approach to both socialist vegetarianism in Japan and Adventist vegetarianism in the United States.
Gesehen am 05.12.2025